Mehko pravo v sodni praksi slovenskih sodišč - Rošic Feguš, Verena (Podjetje in delo, 2020)
In the last three decades at EU level, the role of soft law as acts without a formal legal binding force -also because of the more positive approach of the Court of Justice to these acts - has increased. As national courts must take soft law into account in certain aspects following the established position in the Grimaldi case, this article, through a study of legal theory and case law of Slovene courts, offers an insight into the attitude of Slovenian courts towards EU soft law, as well as national soft law, compares both types of acts regarding their content, functions and possibility of their challenge before the Court of Justice or the Constitutional Court of the Republic of Slovenia, and finally draws a conclusion on the role of soft law in Slovenia.
Keywords: application of soft law; dolžnost upoštevanja mehkega prava; duty to take soft law into account; EU soft law; mehko pravo EU; nacionalno mehko pravo; national soft law; presoja zakonitosti; review of legality; uporaba mehkega prava